Cyber Security Challenges in Syrian Bank Liquidity Management: Maintaining Stability in The Digital Age - Naila Fadilah; Hendri Hermawan Adinugraha (Syamilah Publishing, 2024)
This study explores the challenges facing cybersecurity. by financial institutions, especially the sharia bank, in the context of liquidity management to maintain financial stability in the digital age. The digital age marks the transformation of the financial landscape that gives facility but also poses a cybersecurity risk that Sharia Bank, as a financial entity that implementing the principles of Shariah, especially vulnerable to Cyber attacks that could threaten liquidity and financial stability This research covers an in-depth background on Cyber attacks and liquidity management in sharia banks. Consider the latest theories and related case studies, research This analyzes the impact of cyber attacks on liquidity and stability. Sharia bank finance. As part of the research methodology, the study In-depth literature is used to identify trends, challenges, and strategies related to cybersecurity in liquidity management. Findings This research provides a deep insight into how banks Shariah can face and respond to cybersecurity challenges, as well as strategies that can be applied to maintain stability financial in the digital age. Practical implications and recommendations for Similar financial institutions were discussed, contributing to practical understanding and policy related to liquidity management and cybersecurity. This research provides a better understanding deep on the relationship between cybersecurity and stability financial, providing the necessary framework for banks Shariah and other financial institutions to face the challenge This complex.